Clinical and genetic correlates of suicidal ideation during antidepressant treatment in a depressed outpatient sample. (March 2011) - Perroud, Nader; Bondolfi, Guido; Uher, Rudolf; Gex-Fabry, Marianne; Aubry, Jean-Michel; Bertschy, Gilles; Malafosse, Alain; Kosel, Markus
Aims: This study investigated clinical and genetic predictors of increasing suicidal ideation during antidepressant treatment.Materials & methods: A total of 131 depressed outpatients were allocated to four antidepressants (paroxetine, venlafaxine, clomipramine or nefazodone) in a sequential step procedure until remission. Suicidality was assessed using the 10th item of the Montgomery––Asberg Depression Rating Scale (MADRS). A total of 11 candidate genes involved in different mechanisms of antidepressant action were selected for association with increasing suicidality.Results: Increasing suicidality correlated with depression severity and higher antidepressant blood levels. Risk of increasing suicidal ideation was higher in subjects taking antidepressants other than paroxetine (odds ratio: 1.11). The strongest genetic predictor was found to be rs1360780 within the FKBP5 gene (p = 2.9 ×× 10 -5 ), followed by 2677G>T in the ABCB1 gene. The rs130058 SNP within the 5-HTR1B gene demonstrated a differential association with increasing suicidal ideation depending on antidepressant type.Conclusion: Increasing suicidal ideation might be an adverse effect of antidepressants. The involvement of FKBP5 indicates that dysregulation of the hypothalamic––pituitary––adrenal axis is involved in treatment increasing suicidal ideation. Original submitted 12 October 2010; Revision submitted 18 November 2010.